Failure analysis and mechanical behaviors of metamaterials - Bhuwal, Akash Singh (2023)
In recent years, mechanical metamaterials have been explored for their tunable nature with the continual development of Additive Manufacturing (AM) technologies. As a result, the failure mechanisms of the metamaterials and their mechanical behaviours under different boundary and environmental conditions have been investigated. Firstly, failure mechanisms of AM originated imperfections in the metamaterials have been investigated. In this, three types of imperfection have been considered in the numerical modelling of the metamaterials: distorted struts, missing struts, and strut diameter variation. Then a novel numerical framework was developed to overcome computational difficulties within the existing numerical approaches beyond the elastic region. Three modes of microscopic localisation were observed in metamaterials before failure: crushing band, shear band and void coalescence. The results showed that a clear separation exists between the three modes of localisation depending upon the type and level of defects and loading condition. Under compressive loading, all metamaterials failed due to the crushing band; the distorted lattices are prone to shear band localisation with increased distortion, whereas missing lattices majorly fail due to void coalescence at high missing struts defect.